Pengaruh Price Discount, Online Customer Review dan Rating Terhadap Purchase Intention Pada Aplikasi Booking Hotel Traveloka di Jawa Tengah - Wardhani, Kartika Dinda Kusuma; Nuryanto, Imam (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to examine theories regarding pice discount, online customer reviews and ratings on buying interest on the Traveloka hotel hooking application in Central Java. The population in this study is people who are interestedin using the Traveloka hotel booking application in Central Java. Determination of the sample using purposive sampling method with the number of respondents as many as 134 individuals with analytical techniques using the Statistical Package for the Science (SPSS). The result is that the price discount variable and online customer reviews have an positive effect on purchase intention on the Traveloka hotel hooking application in Central Java. Meanwhile the rating has an effect but not significant on purchase intention on the Traveloka booking application in Central Java.Penelitian ini bertujuan untuk menguji teori-teori mengenai price discount, online customer review dan rating terhadap minat beli pada aplikasi booking hotel Traveloka di Jawa Tengah. Populasi dalam penelitian ini yaitu masyarakat yang berminat menggunakan aplikasi booking hotel Traveloka di Jawa Tengah. Penentuan sampel menggunakan metode purposive sampling, jumlah responden sebanyak 134 individu dengan menggunakan Statistical Package for the Science (SPSS). Hasil variabel price discount dan online customer review berpengaruh positif terhadap purchase intention pada aplikasi booking hotel Traveloka di Jawa Tengah. Sedangkan rating berpengaruh namun tidak signifikan terhadap purchase intention pada aplikasi booking hotel Traveloka di Jawa Tengah. Keywords:price discount, online customer review, rating, purchase intention